Implementasi Kebijakan Pengurangan Sampah Rumah Tangga di Desa Kebonsari Kecamatan Candi Kabupaten Sidoarjo Berdasarkan Peraturan Bupati Sidoarjo Nomor 71 Tahun 2019 - Viandra Rafelia Cahya Sunarko; Kalvin Edo Wahyudi (Universitas Warmadewa, 2025)
The Sidoarjo Regent Regulation Number 71 of 2019 concerning the reduction of household waste is the main guideline in addressing the issue of household waste accumulation in Sidoarjo Regency. This research aims to describe the implementation process of waste management regulations and similar household waste in Kebonsari Village and to identify supporting and inhibiting factors in its implementation. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results show that the implementation of the Sidoarjo Regent Regulation Number 71 of 2019 in Kebonsari Village has been ongoing but not yet optimal, marked by the implementation of the 3R (Reduce, Reuse, Recycle) activities through the waste bank in Kebonsari Village. However, there are still several obstacles, such as limited resources to support policy implementation, limited facilities, and minimal support from the Village Government. Supporting factors in this implementation include the community's understanding of the policy content, clarity of the policy's goals and benefits, political support from various actors, and community involvement in policy implementation. With this regulation, household waste management in Kebonsari Village can be more organized and in accordance with the provisions. This is evidenced by the ongoing management of household waste at the waste bank in Kebonsari Village.